Five‐Year Longitudinal Changes in Treatment Strategies and Clinical Outcomes in Adults With Haemophilia: The ADVANCE Japan Cohort Study - Azusa Nagao; Akihiro Sawada; Takeshi Kanematsu; Naoya Yamasaki; Hideyuki Takedani; Masanori Nojima; Yukio Hiroi; Teruhisa Fujii; Nobuaki Suzuki; Tadashi Matsushita; Satoshi Higasa; Kagehiro Amano; et al. (Haemophilia, 2026)
ABSTRACT Background Prophylactic treatment for haemophilia has evolved with the introduction of extended half‐life (EHL) and nonfactor products. However, long‐term real‐world data describing how these advances have affected adults with haemophilia remain limited. Objectives To evaluate 5‐year changes in treatment strategies and clinical outcomes in adults aged ≥40 years with haemophilia. Methods We analyzed 5‐year longitudinal data from ADVANCE Japan, a nationwide prospective registry of adults aged ≥40 years with haemophilia. Results Of approximately 600 registered participants, 568 inhibitor‐negative individuals were included in this analysis. The median follow‐up duration was 4.99 years (Q1–Q3, 4.89–5.92). In haemophilia A, treatment strategies shifted towards EHL and nonfactor therapies over time. Among participants with severe haemophilia A receiving prophylaxis, median injection frequency decreased from 2.0 to 1.0 injection per week over 5 years ( p < 0.001). In contrast, among participants with severe haemophilia B, injection frequency remained unchanged ( p = 0.563). Despite these therapeutic transitions, annualized bleeding rate (ABR) and annualized joint bleeding rate (AjBR) showed no significant longitudinal changes across age groups in either haemophilia A or B. The proportion of participants with at least one target joint decreased from 88/568 (15.5%) at baseline to 72/548 (13.1%) in 2024. Conclusions Over 5 years, treatment strategies in adults with haemophilia A shifted towards EHL and nonfactor therapies, with reduced injection frequency among severe haemophilia A receiving prophylaxis. Bleeding rates remained stable and target joints modestly decreased, suggesting that bleeding outcomes alone may not fully reflect the evolving clinical burden in aging adults with haemophilia. Trial Registration This study is registered in the Japan Registry of Clinical Trials (JRCT; https://jrct.mhlw.go.jp/latest‐detail/jRCT1030190046 )